25.1k views
2 votes
Please help with these partial fractions!!!

Please help with these partial fractions!!!-example-1
User Sivanes
by
5.9k points

1 Answer

1 vote

a. Factorize the denominator:


(x+14)/(x^2-2x-8)=(x+14)/((x-4)(x+2))

Then we're looking for
a,b such that


(x+14)/(x^2-2x-8)=\frac a{x-4}+\frac b{x+2}


\implies x+14=a(x+2)+b(x-4)

If
x=4, then
18=6a\implies a=3; if
x=-2, then
12=-6b\implies b=-2. So we have


(x+14)/(x^2-2x-8)=\frac3{x-4}-\frac2{x+2}

as required.

b. Same setup as in (a):


(-3x^2+5x+6)/(x^3+x^2)=(-3x^2+5x+6)/(x^2(x+1))

We want to find
a,b,c such that


(-3x^2+5x+6)/(x^2(x+1))=\frac ax+\frac b{x^2}+\frac c{x+1}

Quick aside: for the second term, since the denominator has degree 2, we should be looking for another constant
b' such that the numerator of the second term is
b'x+b. We always want the polynomial in the numerator to have degree 1 less than the degree of the denominator. But we would end up determining
b'=0 anyway.


\implies-3x^2+5x+6=ax(x+1)+b(x+1)+cx^2

If
x=0, then
b=6; if
x=-1, then
c=-2. Expanding everything on the right then gives


-3x^2+5x+6=ax^2+ax+bx+b+cx^2=(a-2)x^2+(a+6)x+6

which tells us
a-2=-3 and
a+6=5; in both cases, we get
a=-1. Then


(-3x^2+5x+6)/(x^2(x+1))=-\frac1x+\frac6{x^2}-\frac2{x+1}

as required.

User Akhil M
by
5.3k points